ASSESSMENT OF APOPTOSIS IN CHRONIC TONSILLITIS: THE ROLE OF CELL DEATH IN THE PATHOGENESIS OF THE DISEASE AND ITS INTERRELATION WITH THE IMMUNE RESPONSE - Lutfullaev G.U; Kobilova Sh.Sh; Madaminova N.E; Karimova Z.Kh; Mirzaev E.M; Mardonov H.Kh (Western European Studies, 2025)
Chronic tonsillitis is a persistent inflammation of the tonsil tissue that occurs due to recurrent acute or subclinical infections. Recurrent and chronic inflammation of the palatine tonsils sometimes leads to hypertrophy. Apoptosis provides an important balance between lymphocytes in the lymphoid tissue of the tonsils. The aim of this study is to study apoptosis in tonsil diseases
Keywords: chronic tonsillitis; apoptosis